Autophagy-associated immune dysregulation and hyperplasia in a patient with compound heterozygous mutations in ATG9A. Issue 2 (1st February 2023) - Hu, Guowu; Hauk, Pia J; Zhang, Nannan; Elsegeiny, Waleed; Guardia, Carlos M.; Kullas, Amy; Crosby, Kevin; Deterding, Robin R.; Schedel, Michaela; Reynolds, Paul; Abbott, Jordan K; Knight, Vijaya; et al.
ABSTRACT: Autophagy involving core machinery proteins such as ATG9A is part of a cytoprotective process whose dysregulation is associated with carcinogenesis, neurodegeneration and autoimmunity, but few examples exist of monogenic diseases to further insights into human disease. In the present studies, we report a patient with novel compound heterozygous mutations in ATG9A after patient and parental DNA were subjected to whole exome sequencing. The patient developed hyperplastic proliferations of T and B cells in lung and brain and exhibited defects in lymphocyte memory cell populations after developing an infection with Epstein-Barr virus (EBV). Peripheral blood leukocytes from the patient exhibited defects in autophagic activity and EBV-transformed cells redemonstrated this defect which was also associated with defective NFKB (nuclear factor kappa B) signaling and accumulation of the pro-proliferative protein MYC (MYC proto-oncogene, bHLH transcription factor) and anti-apoptotic protein BCL2 (BCL2 apoptosis regulator), leading to increased proliferative capacity. Defects were corrected after transformation with plasmids expressing ATG9A and after treatment of cells as well as the patient with the MTOR (mechanistic target of rapamycin kinase) inhibitor, autophagy-inducing immunosuppressant rapamycin. These results point to a novel role of ATG9A and autophagy in human cellular signaling associated with hyperplasia and lymphocyte biology and provide an example how genetic studies may suggest effective specific therapeutic interventions. Abbreviations: BCL2: BCL2 apoptosis regulator; BCL10: BCL10 immune signaling adaptor; CARD11: caspase recruitment domain family member 11; CBM: CARD11-BCL10-MALT1; CR2: complement C3d receptor 2; EBNA: Epstein Barr nuclear antigen; EBV: Epstein-Barr virus; FCGR3A; Fc gamma receptor IIIa; GLILD: granulomatous-lymphocytic interstitial lung disease; HV: healthy volunteer; IKBKB/IKB kinase: inhibitor of nuclear factor kappa B kinase subunit beta; IL2RA: interleukin 2 receptor subunit alpha; MALT1: MALT1 paracaspase; MS4A1: membrane spanning 4-domain A1; MTOR: mechanistic target of rapamycin kinase; MYC: MYC proto-oncogene, bHLH: transcription factor; NCAM1: neural cell adhesion molecule 1; NFKB: nuclear factor kappa B; NIAID: National Institute of Allergy and Infectious Diseases; NK: natural killer; PTPRC: protein tyrosine phosphatase receptor type C; SELL: selectin L; PBMCs: peripheral blood mononuclear cells; TR: T cell receptor; Tregs: regulatory T cells; WT: wild-type